Using Social Media to Improve Communication with Stakeholders in a Local School District - Locklear, Joshua D. (East Carolina University, 2019)
This study examines the impact of social media use as a communication tool within a local school district. Surveys were designed to gauge the effectiveness of communication efforts between district administrators, school administrators, and stakeholders, as well identify the forms of communication that each of the groups prefer. There was a total of 241 participants who completed the surveys, which were administered in three phases. The results were analyzed and used to plan a professional development session for district leaders in which they received training on various social media channels and they were challenged to begin implementing them in their communication with faculty, staff, parents, and community members. The results indicate that transparency between schools and stakeholders positively impacts public perception of local schools, and therefore the school district. It is recommended that district administrators create and implement a comprehensive communication plan, which includes a policy to assist employees in appropriate use of social media.
Keywords: stakeholder communication; Social media in education; Communication in education